Interface Engineering of MoS2/Ni3S2Heterostructures for Highly Enhanced Electrochemical Overall-Water-Splitting Activity - Zhang, Jian; Wang, Tao; Pohl, Darius; Rellinghaus, Bernd; Dong, Renhao; Liu, Shaohua; Zhuang, Xiaodong; Feng, Xinliang (Angewandte Chemie International Edition, 2016)
To achieve sustainable production of H2fuel through water splitting, low-cost electrocatalysts for the hydrogen-evolution reaction (HER) and the oxygen-evolution reaction (OER) are required to replace Pt and IrO2catalysts. Herein, for the first time, we present the interface engineering of novel MoS2/Ni3S2heterostructures, in which abundant interfaces are formed. For OER, such MoS2/Ni3S2heterostructures show an extremely low overpotential of ca. 218 mV at 10 mA cm-2, which is superior to that of the state-of-the-art OER electrocatalysts. Using MoS2/Ni3S2heterostructures as bifunctional electrocatalysts, an alkali electrolyzer delivers a current density of 10 mA cm-2at a very low cell voltage of ca. 1.56 V. In combination with DFT calculations, this study demonstrates that the constructed interfaces synergistically favor the chemisorption of hydrogen and oxygen-containing intermediates, thus accelerating the overall electrochemical water splitting.
CRIS-Team Scopus Importer:2023-03-20
Keywords: electrocatalysts; interface engineering; molybdenum disulfide; nickel sulfide; water splitting